2012
DOI: 10.1371/journal.pone.0038337
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting the Mitochondrial Gene Pool of Modern Panamanians

Abstract: The Isthmus of Panama–the narrow neck of land connecting the northern and southern American landmasses–was an obligatory corridor for the Paleo-Indians as they moved into South America. Archaeological evidence suggests an unbroken link between modern natives and their Paleo-Indian ancestors in some areas of Panama, even if the surviving indigenous groups account for only 12.3% of the total population. To evaluate if modern Panamanians have retained a larger fraction of the native pre-Columbian gene pool in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 46 publications
8
40
2
Order By: Relevance
“…There is some evidence that it might also be present in the Bella Coola tribe (5,44) and among the Ojibwa (5, 45), based solely on the 16111 HVS-I marker. Looking southward, a significant incidence of B2a found in Mexico is confirmed both in tribal groups (42) and general populations (present study), but not in Central America (33,42). Among the two analyzable subclades, defined by a control-region marker (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…There is some evidence that it might also be present in the Bella Coola tribe (5,44) and among the Ojibwa (5, 45), based solely on the 16111 HVS-I marker. Looking southward, a significant incidence of B2a found in Mexico is confirmed both in tribal groups (42) and general populations (present study), but not in Central America (33,42). Among the two analyzable subclades, defined by a control-region marker (Fig.…”
Section: Resultssupporting
confidence: 67%
“…To evaluate this issue, we focused on mitogenomes belonging to two haplogroups, known as A2a and B2a, which are characterized by peculiar geographic distributions. Among the numerous subclades radiating from the root of the panAmerican haplogroup A2 (32)(33)(34), A2a (together with A2b) mtDNAs have been mostly identified only in Siberia, in Alaska, and the surrounding regions, and in Natives from the American Southwest (21,31,(35)(36)(37)(38)(39)(40)(41). B2a radiates from the root of B2, another common pan-American haplogroup.…”
mentioning
confidence: 99%
“…For haplogroup A2 nodes coalesced at 18,000 ± 15,033 YBP (years before present; ρ ± σ = 1.08 ± 0.90). This time estimate falls within the range of other reported dates for haplogroup A2 (Achilli et al 2008;Perego et al 2012;Tamm et al 2007). Contrary to this scenario, haplotypes that belong to the haplogroup B2 coalesced at 1,808 ± 785 YBP (ρ ± σ = 0.10 ± 0.04); however, most recent single mutations emerged around 300 YBP and are more frequent in Rama Cay.…”
Section: Haplotype Network and Chronometrysupporting
confidence: 87%
“…According to the mtDNA molecular clock, haplogroup A2 most likely coalesced around 18,000 YBP. This estimation falls within the most accepted time of colonization of Central America between 15,000 and 19,000 YBP based on mtDNA (Perego et al 2012).…”
Section: Mitochondrial Diversitysupporting
confidence: 66%
“…Aided by the growing data from whole mitogenomes, the five Native American mtDNA haplogroups initially proposed to be "founder" lineages, A-D and X, have been expanded to at least eight maternal monophyletic haplogroups distributed throughout the Americas: A2, B2, C1b, C1c, C1d, C1d1, D1, and D4h3a (Bandelt et al 2003;de Saint-Pierre et al 2012;Fagundes et al 2008;Perego et al 2009;Tamm et al 2007;Torroni et al 1992). Whole mitogenome studies have further refined the phylogenies of these founding haplogroups and have identified unique lineages within them, among which some appear specific to certain geographical regions (Bodner et al 2012;Hooshiar Kashani et al 2012;Perego et al 2012). Regional patterns have been characterized in tandem with reconstructing the emerging complexity of movements from Beringia/Siberia into the American continent.…”
mentioning
confidence: 99%